Cordyceps bassiana inhibits smooth muscle cell proliferation via the ERK1/2 MAPK signaling pathway. Issue 1 (December 2016) - Jin, Enze; Han, Seongho; Son, Mina; Kim, Sung-Whan
Abstract Cordyceps belongs to a genus of acormycete fungi and is known to exhibit various pharmacological effects. The aim of this study was to investigate the effect ofCordyceps species on the proliferation of vascular smooth muscle cells (VSMC) and their underlying molecular mechanism. A cell proliferation assay showed thatCordyceps bassiana ethanol extract (CBEE) significantly inhibited VSMC proliferation. In addition, neointimal formation was significantly reduced by treatment with CBEE in the carotid artery of balloon-injured rats. We also investigated the effects of CBEE on the extracellular signal-regulated kinase (ERK) signal pathway. Western blot analysis revealed increased ERK 1/2 phosphorylation in VSMCs treated with CBEE. Pretreatment with U0126 completely abrogated CBEE-induced ERK 1/2 phosphorylation. In conclusion, CBEE exhibited anti-proliferative properties that affected VSMCs through the ERK1/2 MAPK signaling pathway. Our data may elucidate the inhibitory mechanism of this natural product.